Analisis Strategi Pengendalian dan Faktor-Faktor yang Mempengaruhi Deviasi pada Rencana Penarikan Dana (RPD) Harian di KPPN Bandung II - Rifa Aulia Mahya Afifa; Mas Rasmini (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2026)
This study analyzes the control strategies implemented by KPPN Bandung II to minimize deviations in the Daily Cash Withdrawal Plan (RPD) and identifies the key factors influencing these deviations. RPD deviations pose significant challenges as they affect the accuracy of national cash planning, budget disbursement efficiency, and overall fiscal accountability. Using a qualitative approach through interviews, observations, and document review, the study reveals three primary sources of deviation: the quality of human resources in work units, the performance of information systems (SAKTI and Monsakti), and external variables such as field conditions, regulatory changes, and system disruptions. The findings indicate that KPPN’s control strategies including application-based monitoring, capacity building for work units, and service innovations for accelerating SPM processing vary in effectiveness depending on user readiness and system reliability. The study concludes that managing RPD deviations requires an integrated approach combining technological optimization, human resource development, and flexible service mechanisms to address dynamic operational challenges. With adaptive and collaborative strategies, the accuracy of national cash planning can be maintained more consistently